Road map to clean energy using laser beam ignition of boron-hydrogen fusion. (12th December 2017) - Hora, H.; Eliezer, S.; Kirchhoff, G.J.; Nissim, N.; Wang, J.X.; Lalousis, P.; Xu, Y.X.; Miley, G.H.; Martinez-Val, J.M.; McKenzie, W.; Kirchhoff, J.
Abstract: With the aim to overcome the problems of climatic changes and rising ocean levels, one option is to produce large-scale sustainable energy by nuclear fusion of hydrogen and other very light nuclei similar to the energy source of the sun. Sixty years of worldwide research for the ignition of the heavy hydrogen isotopes deuterium (D) and tritium (T) have come close to a breakthrough for ignition. The problem with the DT fusion is that generated neutrons are producing radioactive waste. One exception as the ideal clean fusion process – without neutron production – is the fusion of hydrogen (H) with the boron isotope 11 B11 (B11). In this paper, we have mapped out our research based on recent experiments and simulations for a new energy source. We suggest how HB11 fusion for a reactor can be used instead of the DT option. We have mapped out our HB11 fusion in the following way: (i) The acceleration of a plasma block with a laser beam with the power and time duration of the order of 10 petawatts and one picosecond accordingly. (ii) A plasma confinement by a magnetic field of the order of a few kiloteslas created by a second laser beam with a pulse duration of a few nanoseconds (ns). (iii) The highly increased fusion of HB11 relative to present DT fusion is possible due to the alphas avalanche created in this process. (iv) The conversion of the output charged alpha particles directly to electricity. (v) To prove the above ideas, our simulations show for example that 14 milligram HB11 can produce 300 kWh energy if all achieved results are combined for the design of an absolutely clean power reactor producing low-cost energy.